Plan de negocios para la creación de musacol empresa comercializadora de meristemos de banano y plátano en santa marta (2023)
MUSACOL is a business idea that is formed to help banana and plantain producers to reduce the economic loss due to banana diseases transmitted in traditional breeding practices, in turn to obtain more product, to establish exact dates of the first harvest, etc. This business idea focuses on the banana is the most important crop in the agricultural sector of Colombia, this food is exported more than 100 million boxes annually, but it is one of the fruit plantations that suffer more diseases and with the production of meristems or clones of their species can reduce much of the risk of deadly diseases. The banana is a crop of nutritional importance because it has many vitamins and minerals (Navarro, 2016). Musaceae (banana) traditionally reproduced through corms, these are the initial part of the plant where its roots sprout, this is considered as the seed. One of the main problems with this type of conventional reproduction is that the multiplication rate is low. Our business plan will allow us to improve the multiplication rate, the quality of the material and many other variables necessary for production. The following research will be of a mixed type, and for this qualitative research is planned, seeking to demonstrate as much as possible the objective of the study.